A alegoria na lírica baudelairiana: uma leitura a partir de Walter Benjamin - Arêas, Joana Pinheiro Gomes (2009)
This dissertation aims to analyse how Walter Benjamin rehabilitates the allegoric form of Charles Baudelaire´s Fleurs du mal poetry and, in doing so, allows for another approach of the poet, revealing his critical character. Through the notions of time and history, Benjamin articulates the allegoric images of the spleen with the symbolic images of the ideal, which offer a critical image of modernity when juxtaposed in the Baudelarian poetry. The presentation of this interpenetration of images, both allegoric and symbolic, makes evident the ambiguity of time in modernity. The retrieval of the allegoric form in Baudelaire is, first of all, the recovery of a historicity and a temporality that reveal time in its senility. The discussion on the rehabilitation of the modern allegory in Baudelaire comes together with the Benjaminian study of the allegory, also present in the baroque drama theatre. Both in the baroque and in modernity, the allegory sheds light on that dimension of historic temporality, which opposes eternity and the plenitude of the symbol